Kinerja Diagnostik Pita Ukuran Standar Tinggi Fundus Uteri Dalam Deteksi Janin Tumbuh Lambat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Infants with intrauterine growth retardation (IUGR) have higher risk of morbidity and mortality compared to infants with appropriate weight for gestational age. Although ultrasonography has been accepted as a reliable tool to detect IUGR, the scarce availability and high cost of the equipment has led to search for less expensive and practical use procedure. A cross-sectional study was carried out to evaluate the diagnostic performance of standardized measurement tape for uterine fundal level in the detection of IUGR. The study consisted of 3 phases: developing the standardized measurement tape, comparing the diagnosis of IUGR using the tape with gold standard, and testing the acceptability of the tape by health workers. The number of sample in this research are 67 women with IUGR infants among 534 women giving birth at Dr. Sardjito Hospital during the study period. The distribution of gestational age was 0.6% at 24-27 weeks, 6.4% at 28-36 weeks and 97.6% at 37-42 weeks. The results show that standardized tape fit with Alibasyah's curve of fundal level at 24-42 weeks of gestational age .in Dr. Sardjito Hospital, Yogyakarta, by applying cut-off points for abnormal fetal growth at 10th percentile for IUGR and 90th percentile for big babies. The standardized tape with high sensitivity, specificity and could be used as an alternative in detecting IUGR in less expensive and more practical way.